2023
DOI: 10.1038/s42003-023-04663-y
|View full text |Cite
|
Sign up to set email alerts
|

The SGLT2 inhibitor empagliflozin improves cardiac energy status via mitochondrial ATP production in diabetic mice

Abstract: Empagliflozin, a sodium-glucose co-transporter 2 inhibitor developed, has been shown to reduce cardiovascular events in patients with type 2 diabetes and established cardiovascular disease. Several studies have suggested that empagliflozin improves the cardiac energy state which is a partial cause of its potency. However, the detailed mechanism remains unclear. To address this issue, we used a mouse model that enabled direct measurement of cytosolic and mitochondrial ATP levels. Empagliflozin treatment signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A recent study in db/db mice showed that EMPA treatment leads to significantly increased cytosolic and mitochondrial adenosine triphosphate (ATP) levels as well as improved maintenance of ATP both during ischaemia/reperfusion (I/R) in isolated hearts and during hypoxia in isolated cardiomyocytes. 13 This study suggests EMPA has a direct metabolic effect on energetics when the heart is stressed either by I/R, hypoxia, HF or diabetes.…”
Section: Introductionmentioning
confidence: 73%
“…A recent study in db/db mice showed that EMPA treatment leads to significantly increased cytosolic and mitochondrial adenosine triphosphate (ATP) levels as well as improved maintenance of ATP both during ischaemia/reperfusion (I/R) in isolated hearts and during hypoxia in isolated cardiomyocytes. 13 This study suggests EMPA has a direct metabolic effect on energetics when the heart is stressed either by I/R, hypoxia, HF or diabetes.…”
Section: Introductionmentioning
confidence: 73%
“…However, hemodynamics were not acutely deteriorated after empagliflozin administration in the present study. Recently, a direct cardiac effect of empagliflozin to improve cardiac energy status is suggested despite the lack of SGLT2 expression in cardiac tissues [ 43 ]. Such an off-target effect of empagliflozin might have helped the failing heart better tolerate the increased afterload.…”
Section: Discussionmentioning
confidence: 99%
“… 35 These changes mirror the effects of SGLT2i on myocardial energy supply, ketonemia, suppression of cardiomyocyte death pathways, and improvements in myocardial flow reserve and vasomotor responses. 35 39 However, the influence of SGLT2i on myocardial function and heart structure, as assessed by echocardiography, has yet to be evaluated in dialysis patients, making it an integral part of the exploratory analysis in this trial.…”
Section: Discussionmentioning
confidence: 99%